A Novel Decision Support Framework for Computing Expected Utilities from Linguistic Evaluations - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

A bi-objective multi-period series-parallel inventory-redundancy allocation problem with time value of money and inflation considerations - Alikar, Najmeh; Mousavi, Seyed Mohsen; Ghazilla, Raja Ariffin Raja; Tavana, Madjid; Olugu, Ezutah Udoncy (Computers & Industrial Engineering)

Application of the NSGA-II algorithm to a multi-period inventory-redundancy allocation problem in a series-parallel system - Alikar, Najmeh; Mousavi, Seyed Mohsen; Raja Ghazilla, Raja Ariffin; Tavana, Madjid; Olugu, Ezutah Udoncy (Reliability Engineering & System Safety)

A redundancy detection algorithm for fuzzy stochastic multi-objective linear fractional programming problems - Khanjani Shiraz, Rashed; Charles, Vincent; Tavana, Madjid; Di Caprio, Debora (Stochastic Analysis and Applications)

A multi-user decision support system for online city bus tour planning - Bagloee, Saeed Asadi; Tavana, Madjid; Di Caprio, Debora; Asadi, Mohsen; Heshmati, Mitra (Journal of Modern Transportation)

A logit-based model for measuring the effects of transportation infrastructure on land value - Asadi Bagloee, Saeed; Heshmati, Mitra; Tavana, Madjid; Di Caprio, Debora (Transportation Planning and Technology)

Recent Fuzzy Generalisations of Rough Sets Theory: A Systematic Review and Methodological Critique of the Literature - Mardani, Abbas; Nilashi, Mehrbakhsh; Antucheviciene, Jurgita; Tavana, Madjid; Bausys, Romualdas; Ibrahim, Othman (Complexity)

A multi-criteria perception-based strict-ordering algorithm for identifying the most-preferred choice among equally-evaluated alternatives - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Setup Optimization Based on Virtual Tooling for Manufacturing in Order to Provide an Intelligent Work Preparation Process - Weber, Jens; Reisch, Raphael-Elias; Schr{\, Christian; Laroque, Christoph

A Multi-User-Collaboration Platform Concept for Managing Simulation-Based Optimization of Virtual Tooling as Big Data Exchange Service - Weber, Jens

Theoretical Concept of Inverse Kinematic Models to determine valid Work Areas using Target Coordinates from NC-programs - Weber, Jens

Sentiment analysis - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Webmonitoring - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing)

Crawler (focused / not focused) - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Text Mining - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Running Out of Words: How Similar User Stories Can Help to Elaborate Individual Natural Language Requirement Descriptions - Baeumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 22nd Conference on Information and Software Technologies (ICIST 2016))

Time models for the classification and identification of production events - Dangelmaier, Wilhelm (Megatrend digitization - potentials of work and company organization)

How to Complete Customer Requirements Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB 2016))

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia Charlotte; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts)

Ein Verfahren zur simulationsgestützten Optimierung von Einrichtungsparametern an Werkzeugmaschinen in Cloud-Umgebungen - Laroque, Christoph; Weber, Jens; Reisch, Raphael-Elias; Schröder, Christian (Nissen, Volker;Stelzer, Dirk;Straßburger, Steffen;Fischer, Daniel (Hrsg.): Multikonferenz Wirtschaftsinformatik (MKWI) 2016)

Multi-criteria scheduling and control in dynamic and stochastic environments: A contribution to the creation of robust schedules for freight handling in air freight terminals - Boxnick, Simon

Intelligent work preparation in the cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt workshop technology online)

Features of IT Service Markets: A Systematic Literature Review (Supplementary Material) - Jazayeri, Bahar; Platenius, Marie Christin; Engels, Gregor; Kundisch, Dennis

Features of IT Service Markets: A Systematic Literature Review - Jazayeri, Bahar; Platenius, Marie; Engels, Gregor; Kundisch, Dennis (Proceedings of the 14th International Conference on Service Oriented Computing (ICSOC))
The provision of IT solutions over electronic marketplaces became prominent in recent years. We call such marketplaces IT service markets. IT service markets have some core architectural building blocks that impact the quality attributes of these markets. However, these building blocks and their impacts are not well-known. Thus, design choices for IT service markets have been made ad-hoc until now. Furthermore, only single aspects of such markets have been investigated until now, but a comprehensive view is missing.In this paper, we identify common features and their interrelations on the basis of a systematic literature review of 60 publications using grounded theory.This knowledge provides an empirical evidence on the interdisciplinary design choices of IT service markets and it serves as a basis to support market providers and developers to integrate market features. Thereby, we make a first step towards the creation of a reference model for IT service markets that provides a holistic integrated view that can be used to create and maintain successful markets in the future.

Dokumentenorientierte NoSQL-Datenbanken in skalierbaren Webanwendungen - Eine Analyse am Beispiel von MongoDB und der Webanwendung PINGO - Bach, Christoph; Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius; Whittaker, Michael (HMD Praxis der Wirtschaftsinformatik)

Residential Energy Storage from Repurposed Electric Vehicle Batteries — Market Overview and Development of a Service-Centered Business Model - Bräuer, sebastian; Monhof, Markus; Klör, Benjamin; Beverungen, Daniel (Proceedings of the IEEE Conference on Business Informatics (CBI 2016))

Can the Crowd Substitute Experts in Evaluation of Creative Ideas? An Experimental Study Using Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 22nd Americas' Conference on Information Systems (AMCIS))

Can the Crowd Substitute Experts in Evaluation of Creative Jobs? The Case of Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Read this Paper! A Field Experiment on the Role of a Call-To-Action in Paid Search - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Geodaten in Social Media als Informationsquelle in Krisensituationen - Mirbabaie, Milad; Tschampel, N.; Stieglitz, Stefan (Proceedings of the 9th Multikonferenz Wirtschaftsinformatik)

Volunteered Geographic Information and its Implications for Disaster Management - Mirbabaie, Milad; Stieglitz, Stefan; Volkeri, S. (Proceedings of the 49th Hawaii International Conference on System Sciences)

Challenge Accepted! - The Impcat of Goal Achievement on Subsequent User Effort and Implications of a Goal's Difficulty - von Rechenberg, Tobias; Gutt, Dominik (Proceedings of the 24th Conference on Information Systems (ECIS), Istanbul)
We empirically investigate the impact of successful goal achievement on future effort to attain the next goal in a recurring goal framework. We use data from a popular German Question & Answer community where goals are represented in the form of badges. In particular, our analysis of this data hinges on the fact, that in this Question & Answer community, badges in a hierarchical badge system are in-creasingly challenging to attain up to a certain badge. After this certain badge, the difficulty level sud-denly drops and remains constant throughout up to the last badge in the hierarchy. Our findings indi-cate that after successful badge achievement users increase their subsequent effort to attain the next badge, but only as long as badges represent a challenge to the user. According to our analysis, we identify self-learning to be the key driver of this behavior.

Goals as Reference Points: Empirical Evidence from a Virtual Reward System - von Rechenberg, Tobias; Gutt, Dominik; Kundisch, Dennis (Decision Analysis)
Heath et al. (1999) propose a prospect theory model for goal behavior. Their analytical model is based on the assumption that goals inherit the main properties of the prospect theory value function, i.e., reference point dependence, loss aversion, and diminishing sensitivity. We investigate whether these main properties transfer to goal behavior in the field. We take user activity data from a gamified Question & Answer community and analyze how users adjust their contribution behavior in the days surrounding goal achievement, where goals are represented by badges. We find that users gradually increase their performance in the days prior to earning a badge, with performance peaking on the day of the promotion. In subsequent days, user performance gradually diminishes again, with the decline being strongest on the day immediately following the badge achievement. These findings reflect the characteristic S-shape of the prospect theory value function which is convex below the reference point and concave above it. Employing the target-based approach, we can interpret the value function as a cumulative density function of a unimodal probability distribution. Our results suggest that it is more likely that active members of the community focus on the next badge relative to the status already achieved, as their next goal and are less likely to focus on more remote (higher-ranked) badges. Our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals.

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Structure and Online Rating Distributions - Herrmann, Philipp; Gutt, Dominik; Rahman, Mohammad (INFORMS Annual Meeting)

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Structure and Online Rating Distributions - Herrmann, Philipp; Gutt, Dominik; Rahman, Mohammad (NBER Summer Institute on the Economics of Information Technology and Digitization)

Money Talks (Even) in the Sharing Economy: Empirical Evidence for Price Effects in Online Ratings as Quality Signals - Gutt, Dominik; Kundisch, Dennis (Proceedings of the 37th International Conference on Information Systems (ICIS), Dublin, Ireland)
Recent literature reports concerns about implausibly high Overall ratings in the sharing economy, which undermines the credibility of this rating as a quality signal. This study empirically investigates the relationship between quality and price, commonly captured by the Value dimension in multidimensional rating systems, to reveal whether reviewers form a perception of quality that they then express in the Value dimension, rather than in the Overall rating. We test our hypotheses on a comprehensive panel dataset for 14,859 Airbnb listings in New York. Our preliminary empirical findings show that an increase in price leads to a significant and substantial decrease in the Value rating, suggesting that Value ratings can offer a valuable source of information for potential buyers in addition to the supposedly inflated Overall rating. Moreover, this mechanism has substantial implications for potential buyers who seek to evaluate a listing’s quality and for a seller’s price setting.

Projekt KUBAS: Koordination ungebundener Vor-Ort-Helfer - Rauchecker, Gerhard; Schryen, Guido (Im Einsatz)

How do different Sources of the Variance of Online Consumer Ratings matter? - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop on IS Design and Economic Behavior (ISDEB))

Factors Affecting the Scientific Impact of Literature Reviews: A Scientometric Study - Wagner, Gerit; Prester, Julian; Roche, Maria; Benlian, Alexander; Schryen, Guido (International Conference on Information Systems)

Development of two novel face-recognition CAPTCHAs: a security and usability study - Schryen, Guido; Wagner, Gerit; Schlegel, Alexander (Computers & Security)
CAPTCHAs are challenge-response tests that aim at preventing unwanted machines, including bots, from accessing web services while providing easy access for humans. Recent advances in artificial-intelligence based attacks show that the level of security provided by many state-of-the-art text-based CAPTCHAs is declining. At the same time, techniques for distorting and obscuring the text, which are used to maintain the level of security, make text-based CAPTCHAs diffcult to solve for humans, and thereby further degrade usability. The need for developing alternative types of CAPTCHAs which improve both, the current security and usability levels, has been emphasized by several researchers. With this study, we contribute to research through (1) the development of two new face recognition CAPTCHAs (Farett-Gender and Farett-Gender&Age), (2) the security analysis of both procedures, and (3) the provision of empirical evidence that one of the suggested CAPTCHAs (Farett-Gender) is similar to Google's reCAPTCHA and better than KCAPTCHA concerning effectiveness (error rates), superior to both regarding learnability and satisfaction but not effciency.
Keywords: CAPTCHA; Usability; Facial features; Gender classiffcation; Age classification; Face recognition reverse Turing test

Supporting Business Model Idea Generation Through Machine-generated Ideas: A Design Theory - John, Thomas (Proceedings of the 37th International Conference on Information Systems (ICIS), Dublin, Ireland)
Successful business model innovation is impossible without innovative business model ideas. When generating such ideas, humans make use of two properties of the human cognitive system: First, their ability to build up knowledge (i.e., raw material for new ideas), and second, their ability to flexibly recombine that knowledge. While these properties enable humans to generate innovative ideas, the amounts of knowledge and cognitive flexibility that humans can possess are limited, which in turn limits human idea generation capability. With business model idea generators, a new class of information systems is proposed that can contribute to alleviating the limits that constrain human idea generation. The ideas that such idea generators produce can complement human business model ideas, thereby increase the probability for high-quality ideas, and eventually raise the odds of successful business model innovation. The contribution is a design theory that describes the architecture of the proposed idea generators.

Does Sentiment Among Users in Online Social Networks Polarize or Balance Out? A Sociological Perspective Using Social Network Analysis - Trier, Matthias; Hillmann, Robert (Understanding Complex Systems)

Business Model Modeling Languages as Tools for Innovation: Theory and Empirical Evidence - John, Thomas

Vergleichende Betrachtung von Software-Werkzeugen zur Geschäftsmodellentwicklung - Strotmeyer, Sebastian; John, Thomas; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik (MKWI))

Disentangling the Relationship Between the Adoption of In-Memory Computing and Firm Performance - Fay, Maria; Müller, Oliver; vom Brocke, Jan (European Conference on Information Systems)
Recent growth in data volume, variety, and velocity led to an increased demand for high-performance data processing and analytics solutions. In-memory computing (IMC) enables organizations to boost their information processing capacity, and is widely acknowledged to be one of the leading strategic technologies in the field of enterprise systems. The majority of technology vendors now have IMC technologies in their portfolio, and the interest of companies in adopting such solutions in order to benefit from big data is increasing. Although there is first research on the business value of IMC in the form of case studies, there is a lack of large-scale quantitative evidence on the positive effect of such solutions on firm performance. Based on a unique panel data set of IMC adoption information and financial firm performance data for a sample of companies from the Fortune 500 list this study aims at explaining the relationship between the adoption of IMC solutions and firm performance. In this research-in-progress paper we discuss the theoretical background of our work, describe the proposed research design, and develop five hypotheses for later testing. Our work aims at contributing to the research streams on IT business value and business analytics by helping to better understand the nature of the interdependencies between IMC adoption and firm performance.

Identifying and quantifying cultural factors that matter to the IT workforce: An approach based on automated content analysis - Schmiedel, Theresa; Müller, Oliver; Debortoli, Stefan; vom Brocke, Jan (European Conference on Information Systems)
Organizational culture represents a key success factor in highly competitive environments, such as, the IT sector. Thus, IT companies need to understand what makes up a culture that fosters employee performance. While existing research typically uses self-report questionnaires to study the relation of culture and the success of companies, the validity of this approach is often discussed and researchers call for new ways of studying culture. Therefore, our research goal is to present an alternative ap-proach to culture analysis for examining which cultural factors matter to the IT workforce. Our study builds on 112,610 online reviews of Fortune 500 IT companies collected from Glassdoor, an online platform on which current and former employees can anonymously review companies and their man-agement. We perform an automated content analysis to identify cultural factors that employees em-phasize in their reviews. Through a regression analysis on numerical employee satisfaction ratings, we find that a culture of learning and performance orientation contributes to employee motivation, while a culture of assertiveness and gender inegalitarianism has a strong negative influence on em-ployees’ satisfaction in the IT workforce. Future research can apply our approach as an alternative method to quantifying culture and its impact on other variables.

Towards an importance-performance analysis of factors affecting e-business diffusion in the wood industry - Trang, S.; Zander, S.; de Visser, B.; Kolbe, L. M. (Journal of Cleaner Production)

Drivers of network governance: a multitheoretic perspective with insights from case studies in the German wood industry - Zander, S.; Trang, S.; Kolbe, L. M. (Journal of Cleaner Production)

A secured context-aware tourism recommender system using artificial bee colony and simulated annealing - Roy, Arup; Tavana, Madjid; Banerjee, Soumya; Caprio, Debora Di (International Journal of Applied Management Science)